Optimal water allocation in the Mekong river basin - Claudia Ringler (University of Bonn, Center for Development Research (ZEF), 2001)
The Mekong River is the dominant geo-hydrological structure in mainland Southeast Asia, originating in China and flowing through or bordering Myanmar, Laos, Thailand, Cambodia, and Vietnam. Whereas water resources in the wet season are more than adequate to fulfill basin needs, there are regional water shortages during the dry season, when only 1-2% of the annual flow reaches the Delta. Recent rapid agricultural and economic development in the basin has led to increasing competition among the riparian countries for Mekong waters. This development calls for a structured approach to the management of the basin, including efficient, equitable, and environmentally sustainable water allocation mechanisms that support the socioeconomic development in the region. Institutional mechanisms for Mekong cooperation among the riparians in the lower basin have been in place since 1957, and were revived in 1995. However, comprehensive water allocation mechanisms for the (lower) basin have not been developed to date. In this study, multi-country and intersectoral analyses of water allocation and use are carried out for the Mekong River Basin with the objective to determine tradeoffs and complementarities in water usage and strategies for the efficient allocation of water resources. An aggregate economic-hydrologic model for the basin is developed that allows for the analysis of water allocation and use under alternative policy scenarios. Results from the analytical framework indicate that although competition for Mekong water still appears to be very low, there are substantial tradeoffs between instream and off-stream water uses. An analysis of alternative water allocation mechanisms shows that to achieve both equitable and large benefits from water uses across countries and sectors, the ideal strategy would be to strive for optimal basin water use benefits and then to redistribute these benefits instead of the water resource. The development of such an integrated framework of analysis can be a critical first step to overcome some of the obstacles to effective management and joint cooperation in the Mekong River Basin. It could also facilitate the upcoming negotiations of water allocation rules in the lower basin and thus contribute to the reasonable and equitable utilization of Mekong River waters, as envisioned in the 1995 Mekong Agreement.
Keywords: 330; Resource /Energy Economics and Policy; Wasserversorgung; Gemeingüter; Wasserpolitik; Internationale Zusammenarbeit; Fluss; Geologie; Ressourcenökonomik; Umweltökonomik; Wirkungsanalyse; Mehr-Länder-Modell; Theorie; Mekong; Greater Mekong